Indonesia’s Online Loan Challenges: What Legal Actions Can Solve the Most Pressing Issues? - Admiral Admiral; Suparto Suparto; Esy Kurniasih; Selvi Afriani; John Woodward; Fadhel Arjuna Adinda (Jurnal Pengabdian Hukum Indonesia (Indonesian Journal of Legal Community Engagement) JPHI, 2025)
The rapid growth of online lending platforms in Indonesia has introduced significant challenges, particularly regarding predatory lending practices, lack of consumer awareness, and insufficient regulatory oversight. These challenges have raised concerns about consumer protection, the exploitation of borrowers, and the need for stronger legal frameworks to ensure fair and transparent lending practices. This paper explores the key legal and regulatory actions necessary to address these pressing issues. It examines the role of Indonesia's Financial Services Authority (OJK) in regulating online lenders and proposes potential improvements in licensing, supervision, and enforcement. The paper also suggests the introduction of clearer lending standards, such as interest rate caps and transparent fee structures, alongside stronger consumer protection laws to prevent harassment and over-indebtedness. Data privacy and security concerns are addressed, with a call for more robust protections around borrower data. Additionally, the paper advocates for financial literacy programs to empower borrowers with the knowledge to make informed decisions. The research contributes to the existing body of knowledge by providing an in-depth analysis of the legal gaps within Indonesia’s online lending market, offering comparative insights from other countries like India and the Philippines, and proposing actionable legal solutions. It also emphasizes the importance of integrating technology into the regulatory process to enhance oversight and consumer protection. Ultimately, this study aims to inform policymakers, regulators, and stakeholders in Indonesia’s fintech industry about the necessary legal reforms to create a more transparent, equitable, and secure online lending environment.